Top 50 Most-Cited Publications on Blepharoplasty Surgery Between 2015 and 2022: From a Current Altmetric Perspective of Research Impact - Evereklioglu, Cem; Sener, Hidayet; Horozoglu, Fatih (Indian Journal of Plastic Surgery, 2023)
Background Blepharoplasty is one of the most-performed esthetic operations, and social media platforms have become an influential tool for distributing scientific information. Because the internet has gained popularity among medical experts and surgeons to connect with the public, we aimed to evaluate the altmetric–bibliometric analysis of the top 50 most-cited articles on blepharoplasty surgery between 2015 and 2022 and assess correlations with various metrics.Methods “Blepharoplasty” was searched using the WoS database, and the altmetric score was obtained. Co-authors, keywords, country of authors, and cited journal network map analysis were created using VOSviewer for the 485 publications retrieved. The articles' focus was examined quantitatively and the most prolific parameters were identified.Results The most research was performed by the USA, the most productive institution was the “University of California System,” and the most prolific author was “Wonn CH.” The number of citations ranged from 37 to 9, and altmetric attention scores ranged from 54 to 0. The most articles and citations peaked in 2021. Altmetric and Twitter scores were moderately correlated with journal metrics but there were no correlations with citation counts.Conclusion The first comprehensive altmetric analysis on blepharoplasty surgery offers new guidelines for upcoming articles by demonstrating the recent investigation trends, prolific parameters, and zones with potential for the public's attention and education, providing valuable data regarding the distribution of scientific knowledge in social media platforms and to the general public. A social network may be used to increase the visibility of scientific articles apart from creating brands and markets.
Keywords: altmetric; blepharoplasty; correlation; Facebook; social media